2022
DOI: 10.1371/journal.pone.0270690
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial diversity and inter-specific phylogeny among dolphins of the genus Stenella in the Southwest Atlantic Ocean

Abstract: The genus Stenella is comprised of five species occurring in all oceans. Despite its wide distribution, genetic diversity information on these species is still scarce especially in the Southwest Atlantic Ocean. Some features of this genus can enhance opportunities for potential introgressive hybridization, e.g. sympatric distibution along the Brazilian coast, mixed known associations among species, karyotype uniformity and genome permeability. In this study we analyzed three genes of the mitochondrial genome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The results highlighted here are consistent with those previously published on the genus Stenella (Faria et al 2022). For many species of Stenella, genetic diversity is high compared to other Delphinidae species (e.g.…”
Section: Striped Dolphinsupporting
confidence: 92%
“…The results highlighted here are consistent with those previously published on the genus Stenella (Faria et al 2022). For many species of Stenella, genetic diversity is high compared to other Delphinidae species (e.g.…”
Section: Striped Dolphinsupporting
confidence: 92%
“…The latter are indicated by red labels describing the mutated nucleotide position with respect to the first sequence in the dataset (Hap-1). et al 10.3389/fmars.2023.1088598 (driven by anthropogenic disruption of biological genetic patterns) representing a crucial point for the implementation of effective conservation measures (Faria et al, 2022). In effect, understanding anthropogenic hybridization dynamics can help identify effective and timely management actions for threatened species avoiding genomic extinction potentially led by the presence of admixed individuals and by human disturbances that cause hybridization (Santostasi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Archer and Perrin (1999) hypothesized a polygynous mating system (one male mates with multiple females during a breeding season) for striped dolphins off Japan, but it is unknown whether striped dolphins in the Gulf of Corinth have a similar system. Regarding other species of the genus Stenella considered to be closely related to striped dolphins (Faria et al, 2022), Perrin and Mesnick (2003) concluded that the mating system of spinner dolphins in the eastern tropical Pacific varies geographically, from a more polygynous mating system in eastern spinner dolphins S. l. orientalis , to a more polygynandrous system in Gray's spinner dolphins S. l. longirostris , where sperm competition may play an important role. A study on spinner dolphin ecotypes by Andrews et al (2013) reported either a possible polygynous mating system (males being preferred by females based on their morphology), or a possible polygynandrous system (where male morphology does not drive sexual selection), depending on ecotype.…”
Section: Discussionmentioning
confidence: 99%